Expectations of Representatives of the Polish Generation (Z)Alpha regarding Stable and Transparent Employment Conditions: A Survey Study - Paweł ŁUCZAK; Izabela RÓŻAŃSKA-BIŃCZYK (Communications of International Proceedings, 2024)
The study explores the expectations of Generation (Z)Alpha, specifically in Poland, regarding stable and transparent employment conditions. The research addresses the growing significance of Generation (Z)Alpha in the labor market, noting how their digital upbringing shapes their distinct needs in the area of stable and transparent work conditions. Using a sample of 446 respondents aged 19 to 22, the study employed the CAWI method to assess their expectations. Key findings indicate that salary remains a dominant factor in job attractiveness, while flexibility in working hours, remote work, and part-time opportunities are highly valued. Gender differences also emerged, with women prioritizing career development and pay equality, while men favored working-time flexibility. The study highlights the importance of adapting employment policies to accommodate these emerging expectations to attract and retain Generation (Z)Alpha employees. This work fills a gap in the literature and emphasizes the need for further research across different regions.
Keywords: Generation (Z)Alpha; work condition; UE Directive